Optimation of Spirulina sp. Growth in Walne Media with Variation of Urea and NaHCO3 Supplements - Lusiana Novia Caturwati; Retno Herrani Setyati (Universitas Gadjah Mada, 2020)
One alternative biofuel to substitute fossil fuels is bioethanol. Microalgae Spirulina sp. contains high carbohydrates, which has 17-25% potential to produce bioethanol. Urea and NaHCO3 can be used as additional nutrients sources of nitrogen and carbon to Spirulina sp. cultivation. Deficiency of nitrogen causing the cell’s enzymes change that shown through decreased lipid and chlorophyll synthesis. While deficiency of carbon can affect the growth rate. In this research, the growth rate of Spirulina sp. is analyzed using Optical Density (OD) method. The growth rate calculation is used to measure the growth of microalgae cells shown in the growth curve. This was a laboratory-scale method using CRD with 4 treatments and 5 replications namely treatment A addition of 0.36 g/500 ml urea without addition of NaHCO3, treatment B addition of 0.043 g/500 ml NaHCO3 without addition of urea, treatment C addition of 0.36 g/500 ml urea and 0.043 g/500 ml NaHCO3, and control without addition of urea or NaHCO3. The results indicated that addition of urea and NaHCO3 didn’t affect to OD and Spirulina sp. growth rate. The highest growth rate was treatment A with 0.00906/day of growth rate followed by treatment C which has 0.00865/day of growth rate. Treatment B and control treatment (K) showed a low growth rate. The maximum OD value obtained in treatment C was 0.674 cells/ml on the 10th day. This research can be used as the reference to larger scale of Spirulina sp. cultivation in the field of bioethanol production.